Efektivitas Efektivitas Metode Al Miftah lil Ulum dalam Memahami Ilmu Nahwu pada Santri Madrasah Tsanawiyah Mambaus Sholihin - Humayro Toha; Wildana Wargadinata (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2023)
The use of a method in certain learning aims to present material in a concise, practical and easy to understand manner. This research is considered important to review how far the effectiveness of this method is for the students of MTs Mambaus Sholihin in understanding nahwu science. The method used in this study is a qualitative method because it is a research process that produces descriptive data in the form of written or spoken words from the people being observed. Based on observations of several teachers, it was explained that by using the Al-Miftah lil Ulum method, the Nahwu learning scores of the students experienced a pretty good increase. From the results of the research, the Al-Miftah method has proven to be effective in facilitating students in understanding nahwu science, although basically this method is not the main reference for learning nahwu material at Islamic boarding schools, this method is effective in helping students to recognize and understand nahwu science.